Shipwreck Artifacts from the S.S. Otago and the S.S. Tairoa as Symbols of Dominant Maritime Regional Identity Narratives in Southeastern New Zealand - (:unkn) unknown (My University, 2020)
This article considers the actions of social actors and organizations, who through engaging with artifacts from the wrecks of the nineteenth-century S.S. Otago and S.S. Tairoa, have helped affirm the dominance of shipwreck-based maritime heritage and identity narratives along, or near, the region of the southeastern coast of New Zealand called The Catlins. Those actions are considered through: exploring some episodes of salvaging and exhibiting objects, providing commentary about the way that those actions and objects interact with identity formation and affirmation processes, and examining the connection between local communities and a not-so-distant past. The notion of engagement with material objects leading to their gaining in status/agency, and becoming dominant elements within the negotiation of a shared regional identity and brand, is also considered, along with associated notions of materiality and links between landscape and identity.
Keywords: Maritime history; maritime archaeology; material culture; shipwrecks; iden-tity; regional identity; regional branding; heritage; nautical history; New Zealand; nine-teenth century; Otago; Southland; The Catlins